Skenario Kebijakan Tentang Ruang Terbuka Hijau Di Kota Batu: Suatu Pendekatan Simulasi (Kolaborasi : Jurnal Administrasi Publik, 2022)
Steps to create environmental comfort in Batu City, East Java, need to support sustainable development. This research aims to develop policy scenarios related to simulation-based Green Open Space (RTH) planning to realize Batu City's environmental sustainability. The study of stakeholder preferences for the function of green space is carried out by digging primary data from the relevant parties (stakeholders) using interviews and observations. The green open space in Batu City is decreasing due to the conversion of the RTHK function into a built area. The change in RTHK was caused by the implementation of Batu City development activities which were more inclined to infrastructure development as well as physical facilities and infrastructure. Policy analysis is carried out by conducting simulations (changes to model parameters) and then observing their behavior. Several green open space planning scenarios were carried out using the Powersim constructor software. Several scenarios are related to green open space planning in Batu City, including free scenario, moderate scenario, and sustainable scenario. Of the three scenarios, the sustainable scenario is more suitable because the increase in land ares used in the sustainable scenario is relatively controlled. There are efforts to allocate green open space on residential land, industrial land, social and social facilities land, trade and service land every year to reduce the decrease in green open space.
Keywords: green open space; policy; simulation; sustainable